Dyfuzja produkcji w klasie światowej (ang. „World Class Manufacturing”) wewnątrz łańcucha tworzenia wartości (na przykładzie Fiat Auto Poland SA) - Walczak, Maciej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
The paper presents the concept of World Class Manufacturing (WCM) and the most important components of this system. Next, the main directions of diffusion of WCM in multiplant enterprises, with numerous links with suppliers, were presented. The author is of the opinion that direction of diffusion of WCM depends on the point in the value chain at which the implementation of WCM begins. An example of WCM implementation is the case of Fiat Auto Poland SA which was presented in the paper. The used research methods are studies of domestic and foreign literature, combined with reference to a practical example.
Keywords: World Class Manufacturing; Fiat Auto Poland SA; FCA Poland SA; production management